The Influence of Training and Educational Beackground on The Employee Performance of Bank Rakyat Indonesia Kanca Bukittinggi With The Meadiation of Job Satisfcation - M. Yasril; Harif Amali Rivai; Laura Syahrul (Dinasti Research, 2024)
The aim of this research is to analyze the factors that influence employee performance at work, including training and educational background on employee performance with the employee’s job satisfaction as a mediating variable. Employee performance is an important thing that must be considered by management of a company in achieving company’s goals. The population of this research were the employees of Bank Rakyat Indonesia Kanca Bukittinggi with a sample of 67 people who were employees with the job position of Mantri. The analytical methode used descriptive statical analysis and factor description analysis used SmartPLS 4.0. The result of this study shows that training and eductional background have a positive and significant effect on job satisfaction; training and educational background have a positive and significant effect on employee performance; job satisfaction as a mediating variable has a partial mediating effect in mediating training on employee performance and job satisfaction as mediating variables also has a partial mediation effect in mediated the relationship of educational background towards employee performance.